THE IMPACT OF SUPREME COURT DECISION FOR EFFORTS OF NOTARY OFFICE QUALITY AND COMPETENCY IMPROVEMENT HELD - Yovita Pradita Abimanyu; Pieter Latumeten (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
This study discusses the Notary Appointment Examinations and Notary Office Quality Improvement Training organized by the Ministry of Law and Human Rights in collaboration with Notary Organizations. These efforts were later cancelled due to a Supreme Court Decision. These efforts were made to increase the quality and competence of Notaries. The study's concerns include efforts to raise the standard and proficiency of the Notary Office held by the Ministry of Law and Human Rights and the Notary Organization, as well as the impact of the Supreme Court's ruling on aspiring notaries, the Ministry of Law and Human Rights, and notary organizations. With the help of a document study on secondary data obtained through a literature search, this research is normative and uses the data collection method. Utilizing qualitative is the analytical approach. According to the findings of this study, the Ministry of Law and Human Rights intends to modify the Notary Office Law's appointment requirements to increase the calibre and expertise of notaries, as the Supreme Court has only previously permitted the Notary Ethics Code Examination as a filter. The study concludes that additional systematics are required in addition to Notary Education and the Notary Ethics Code Examination in order to be able to raise the standard and proficiency of the notary position.